ClimaWATCH: A new interactive tool for community heat-health vulnerability assessments - Aparna Keshaviah; Dheeya Rizmie; Huihua Lu; Mike Rudacille; Eric Morris; Colleen Psomas; Farid Qamar; Xindi C. Hu (The Journal of Climate Change and Health)
Introduction: Extreme heat is the deadliest of all weather-related hazards, yet also the most preventable. To boost heat preparedness and response, officials need information on where heat-related health issues concentrate and how risks vary by demographic, social, environmental, and infrastructural factors. We present a tool for heat-health vulnerability assessments, called ClimaWATCH, which links large, diverse data to summarize county, state, and national exposure to heatwaves; susceptibility based on various factors; and heat-related health burdens. Case presentation: Leveraging a case-crossover study design, the tool clarifies how heat-related excess healthcare utilization and spending varies by geography, year, diagnosis, subpopulation, and care setting. Nationally in 2020, excess Medicaid spending amounted to $18 million on heat stress, $15 million on electrolyte imbalance, $25 million on acute myocardial infarction, and $133 million on acute renal failure. Per-beneficiary levels of excess spending on these four acute diagnoses were highest in Massachusetts, Pennsylvania, and California. Discussion: The dynamic functionality can improve emergency preparedness by facilitating exploration of the heterogeneity in heat-related health effects from year to year and by demographic or community feature, heatwave definition, and geographic region. Conclusion: Chief heat officers, public health officials, philanthropic organizations, and others can use ClimaWATCH to develop data-driven, tailored heat action plans to address the needs of different vulnerable populations effectively and equitably, prioritize interventions based on their potential for impact, and improve community and health system resilience to extreme heat.